Headache due to spontaneous spinal cerebrospinal fluid leak secondary to cerebrospinal fluid-venous fistula: Case series. (December 2019) - Duvall, Jaclyn R; Robertson, Carrie E; Cutsforth-Gregory, Jeremy K; Carr, Carrie M; Atkinson, John LD; Garza, Ivan
Objective: Cerebrospinal fluid-venous fistula is an uncommon cause of spontaneous spinal cerebrospinal fluid leak (SSCSFL). We aim to describe the clinical presentation, imaging evaluation, treatment and outcome of SSCSFL secondary to cerebrospinal fluid-venous fistula. Methods: A retrospective review was undertaken of SSCSFL cases secondary to cerebrospinal fluid-venous fistula confirmed radiologically or intraoperatively, seen at our institution from January 1994 to March 2019. Cases with undetermined SSCSFL etiology, alternative etiology or unconfirmed fistula were excluded. Results: Forty-four of 156 patients met the inclusion criteria (31 women, 13 men). Mean age of symptom onset was 52.6 years (SD 8.7, range 33–71 years). Headache was the presenting symptom in almost all, typically daily (69%), and most often in occipital/suboccipital regions. Headache character was most commonly pressure (38%), followed by throbbing/pulsing (21.4%). Orthostatic headache worsening occurred in 69% and an even greater percentage of patients (88%) reported Valsalva-induced headache exacerbation or precipitation. Headache occurred in isolation to Valsalva maneuvers in 12%. Of 37 patients with documented cerebrospinal fluid opening pressure, 13% were <6 cmH2 O; 84%, 7–20 cmH2 O; and one, 25 cmH2 O. Fistulas were almost exclusively thoracic (95.5%). Only one patient responded definitively to epidural blood patch (EBP). Forty-two patients underwent surgery. Most improved following surgery; 48.7% were completely headache free and 26.8% had at least 50% improvement. Conclusion: In our series, cerebrospinal fluid-venous fistula was associated with a greater occurrence of Valsalva-induced headache exacerbation or precipitation than orthostatic headache and did not respond to EBP. Surgery provided significant improvement. Cerebrospinal fluid-venous fistula should be considered early in the differential diagnosis of Valsalva-induced ("cough") headache.